(untitled) (Світ фінансів, 2017)
Ніконенко У. Ресурсозалежна економіка: концептуалізація проблеми. Розглянуто проблему ресурсозалежної економіки з позицій теорій “ресурсного прокляття” та “голландської хвороби”. Систематизовано основні погляди на проблему надлишку природних ресурсів в працях вітчизняних та зарубіжних економістів. Виокремлено позитивні та негативні ефекти надлишку природних ресурсів. Запропоновано модернізацію інституційного механізму реформ. Nikonenko U. Resource dependence of economy: problem conceptualization. The article deals with the problem of resource dependence of economy in contest of “resource curse” and “Dutch disease” theories. The basic views on the problem of natural resources abundance in the works of local and foreign economists are systemized. Positive and negative effects of natural resources abundance are signed. The modernization of institutional mechanism of reforms are proposed.